People who inject drugs (PWID) and HIV/aids cases in Mexico City: 1987-2015 - Martha Romero Mendoza; Denize Meza-Mercado; Rosario Martínez-Martínez; Carlos Magis-Rodríguez; Arturo Ortiz Castro; Maria Elena Medina-Mora (BMC, 2019)
Abstract Background The purpose of this study is to describe the characteristics of individuals who inject drugs, to explore use trends in the past 25 years, and to review the profile of users of various drugs, both legal and illegal, that have been used intravenously without medical prescription in Mexico City. Methods Information was drawn from the Drug Information Reporting System (SRID, 1987-2015) and data from the National Center for the Prevention and Control of HIV/aids (CENSIDA, 1983-2018). SRID is based on two 30-day cross-sectional evaluations carried out during June and November. It has served as an uninterrupted epidemiological surveillance system for 32 years, operating both in health and justice institutions in Mexico City and the metropolitan area. The timely identification of changes in use patterns is regarded as the most consistent tool to track the trajectory of the phenomenon. CENSIDA cases were analyzed based on the number of HIV and aids positive injectable drug users during the same period of time in Mexico City. Results Cocaine users represented the highest number of cases, with a total of N = 293. Back in 2000, the use of this substance showed a significant increase of up to 50%. In turn, heroine and opiates user trends by sex increased from being almost non-existent in 1987 to 13% in 1994. Results provide evidence of the changes in the number of users over the years, with the largest increases being recorded in 1996 (16.5%), 1999 (17%), and 2010 (13%). Conclusions The increase observed in the results coincides with domestic and world political situations that have caused an upturn in the use of some substances over the years. It is not far-fetched to think that in the coming years there will be an increase in the number of individuals who inject drugs due to the high production and availability of heroin in Mexico and the emergence of fentanyl use as indicated by ethnographic research in Mexico City and the deaths linked to its consumption. The latest reports, published in 2018, documented at least five cases of fentanyl users.